Bahan Alam SebagaiSumber Penciptaan TataArtistikNaskahRepublik Reptil Karya Radhar Panca Dahana - Agus Arieyanto (Saraswati)
The stage play is a picture of the scene that is realized by the stage manager in a play. adapted to the demands of the story, will of artistic director. designing the stage to consider some elements of composition that need attention. Well, perspective, volume, content, harmonization, levelitas space. Because the whole object on the stage and used by actors to form a unified whole. Cosmetology mean changing facial appearance became more perfect to describe the character. Fashion is all the accompanying equipment to describe the character. including all accessories and all elements attached to clothing. Keywords: theater, stage, dressing, fashion